Involvement of Spinal Cord Bdnf in the Generation and Maintenance of Chronic Neuropathic Pain in Rats - Hernandez-Kunstmann, A; Constandil-Cordova, L (2011)
Brain-derived neurotrophic factor (BDNF) is involved in neuronal survival and synaptic plasticity of the central and peripheral nervous system. In chronic pain, plastic changes in dorsal horn neurons contribute to a phenomenon of hypersensitivity to pain sensation that is maintained over time, known as central sensitization. This process is accompanied by BDNF overexpression, but the role of BDNF in the generation and maintenance of the hyperalgesic phenomenon is still unclear. The present study was aimed to investigate if exogenous BDNF administered to the rat spinal cord, in addition to trigger pain, participates in the maintenance of the central sensitization process (i.e., pain persistence) and to determine if the pain generated is comparable to that observed in a neuropathic pain model. Results showed that a single intrathecal injection of 0.003. ng of BDNF was able to decrease the nociceptive threshold (Randall-Selitto test) in normal rats, for at least a 42-day period. Furthermore, the hyperalgesia generated was comparable to that observed in rats with a 42-day history of mononeuropathy. Increasing the dose or administering additional doses of BDNF resulted neither in additional effectiveness in reducing the pain threshold nor in the prolongation of the hyperalgesic effect, thus showing that central sensitization induced by BDNF is a dose-independent, all-or-none process. It is concluded that BDNF alone is sufficient for generating a long-lasting neural excitability change in the spinal cord via tyrosine kinase B receptor signaling, similar to that observed in chronic pain models such as neuropathy. © 2011 Elsevier Inc.